Patch test in chronic urticaria as a diagnostic investigative tool - A study in a tertiary care center - Shwetha F Dyamannavar; K A K Surendran; Tukaram Sori; Veeresh Dyavannanavar (Wolters Kluwer Medknow Publications, 2024)
Background: Chronic urticaria (CU) is associated with diverse clinical presentations and varied etiology. Contact allergy plays a critical role in the etiopathogenesis of CU; thus, a patch test can be helpful in identifying potential contact allergens. Aims and Objectives: The aim and objective of this study were to study the causative contact allergen in CU using the Indian Standard Battery allergens approved by the Contact and Occupational Dermatoses Forum of India and to establish the use of patch test in CU. Materials and Methods: One hundred clinically diagnosed cases of CU patients attended to the dermatology department for 2 years were evaluated with detailed history and clinical examination and a patch test was done using the Indian standard series. The patches were removed after 48 h and a reading was taken after 30 min. Observations were graded according to the International Contact Dermatitis Research Group recommendations. Results: Hospital-based prevalence of CU among patients attending the dermatology outpatient department was 3%. A positive patch test was observed in 30% of our study cases. Nickel sulfate was the most common allergen followed by fragrance mix. Patch test positivity was more in housewives, followed by farmers, teachers, and construction workers. Conclusion: The patch test can be used as a diagnostic investigative tool for the etiological diagnosis of CU.